Perilaku Dalam Organisasi Individu - Muhammad Muhammad; Kasful Anwar; Jamrizal Jamrizal (Lembaga Pengembangan Kinerja Dosen, 2024)
Initially, the organization was a bridge in forming a component that could be used as a member to solve a problem. The essence of a learning organization is the organization's ability to utilize the mental capacities of all its members to create the kind of process that will improve it.Organizations where people continually develop their capacity to create the results they truly desire, where new and evolving patterns of thinking are fostered, where group aspirations are given freedom, and where people are continually learning studying (learning to learn) something together, but in general organizations have become a discourse in activities that can be used as part of a group. Basically, this is because humans are social creatures, which in this context is homo socius. This fact is a natural characteristic.It is impossible for humans to live alone, apart from society, groups or living with their communities. Humans are creatures that think and can develop. Every human being has the instinct to live in society. To fulfill these various needs, humans must collaborate because they will not be able to fulfill their own needs. That is where the level of human limitations is a reflection that humans need cooperation and that forum is found in organizations.